Faktor-Faktor yang Mempengaruhi Kapabilitas Internal Audit : Kapabilitas Internal Audit, Kompetensi, Independensi, Pengalaman Audit - Riatno Jonni Parulian; Deliana Deliana; Cris Kuntadi (Dinasti Review, 2023)
Previous research or relevant research has a very important role in scientific research or articles. Previous research or relevant research is used to strengthen theory and explain the relationship or influence between variables. In this article, a review of the factors that influence internal audit capability is carried out, namely competence, independence, and audit experience, based on audit literature studies. The purpose of writing this article is to develop a hypothesis regarding the influence between variables that will be used in further research. The results of the literature review in this article are as follows: 1) competency has an influence on internal audit capability; 2) independence has an influence on internal audit capability; and 3) audit experience has an influence on internal audit capability.